MEWUJUDKAN NILAI TOLERANSI UNTUK MENCIPTAKAN PERDAMAIAN PADA PERSAINGAN BISNIS EKONOMI SYARIAH - Susanti; Zilan Salsabila; Rizal Maulana (STKIP Subang, 2024)
ABSTRACT Tolerance is an important moral attitude in maintaining harmonious relationships, both in social life and the business world. This research aims to analyze the role of tolerance in creating a healthy and ethical business, in accordance with Islamic principles, such as tawhid, trust, and justice. The research method used is a descriptive qualitative approach by analyzing Islamic principles and their application in the business world. The results show that by upholding the values of tawhid, trust, and justice, business actors are able to create a sustainable, fair, and conducive business environment. In addition, tolerance plays an important role in preventing negative competition that can damage relationships between business actors, disrupt cooperation, and create injustice in the market, which has the potential to cause conflict and reduce business reputation. Keywords: Tolerance, Business Competition, Peace